Good morning Maisy [videorecording (DVD)]. - Nielsen, Leo (Universal, 2004)
Join Maisy the lovable mouse and all her friends for adventure and good times. It's a fun-filled morning for Maisy when she drives a choo-choo train, learns to count with her animal friends, and helps with the harvest on the farm.